Environmental impact modeling of selective laser sintering processes. Issue 6 (20th October 2014) - Kellens, Karel; Renaldi, Renaldi; Dewulf, Wim; Kruth, Jean-pierre; Duflou, Joost R.
Abstract : Purpose: – This paper aims to present parametric models to estimate the environmental footprint of the selective laser sintering (SLS)' production phase, covering energy and resource consumption as well as process emissions. Additive manufacturing processes such as (SLS) are often considered to be more sustainable then conventional manufacturing methods. However, quantitative analyses of the environmental impact of these processes are still limited and mainly focus on energy consumption. Design/methodology/approach: – The required Life Cycle Inventory data are collected using the CO2PE! – Methodology, including time, power, consumables and emission studies. Multiple linear regression analyses have been applied to investigate the interrelationships between product design features on the one hand and production time (energy and resource consumption) on the other hand. Findings: – The proposed parametric process models provide accurate estimations of the environmental footprint of SLS processes based on two design features, build height and volume, and help to identify and quantify measures for significant impact reduction of both involved products and the supporting machine tools. Practical implications: – The gained environmental insight can be used as input for ecodesign activities, as well as environmental comparison of alternative manufacturing process plans. Originality/value: – This article aims to overcome the current lack of environmental impact models, covering energy and resource consumption as well as process emissions for SLS processes.